PENERAPAN PENDEKATAN EXPERIENTIAL LEARNING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN BERPIKIR KRITIS PADA SISWA SEKOLAH DASAR - Garnalis, Winda; Nurasiah, Nurasiah; Lyesmaya, Dyah (Program Studi PGMI, 2018)
The purpose of this research done to described the application of experientiallearning approach in their experiences IPA to increase the skills to critical think of primary school student. Methods and models was used in the study research is classroom action research ( CAR ) kemmis and taggart model, which consisted of two cycles. The subject of study this research grade students of 5.3 in SDN Cipanengah CBM Kota Sukabumi which involved 30 student. The results of cycle I showed that the students critical think skills gain a classical mastery of 46,6 %, this is a of 41,81 % improvement of the pretest with classical mastery of 4,79 %. Cycle II showed that the students critical think skills gain a classical mastery of 100 %. The research concluded that through the application of experiential learning approach can increase the skills to think critical of students in learning IPA of grade 5.3 SDN Cipanengah CBM Kota Sukabumi academic year 2017/ 2018.